Optimizing vocabulary mastery through augmented reality flashcards in early primary EFL learners - Nabila Shafa Fikriyyah; Eva Nikmatul Rabbianty (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
Vocabulary mastery plays a crucial role in supporting young learners’ English proficiency; however, many primary school students continue to struggle with retaining new words due to limited exposure and monotonous instructional methods. Although recent technological advancements, particularly Augmented Reality (AR) have shown, promise in enhancing learners’ engagement and multisensory processing, empirical evidence on AR-based vocabulary learning for early primary EFL students remains limited. This study investigates whether there is a significant difference in vocabulary mastery between second-grade students before and after being taught using Augmented Reality (AR)-Based Flashcards at SDI Al-Munawwarah Pamekasan and determines the magnitude of the effect of this intervention on their vocabulary mastery. A quantitative approach was employed using a one-group pretest–posttest pre-experimental design involving 32 second-grade students selected through total sampling. Data were collected using a picture-based vocabulary test administered before and after the intervention, which consisted of two AR-supported learning sessions. The data were analyzed using the Wilcoxon Signed-Rank Test and effect size calculation. The findings reveal a significant improvement in students’ vocabulary mastery, as indicated by an increase in the mean score from 16.81 in the pretest to 18.69 in the posttest. The Wilcoxon Signed-Rank Test shows a statistically significant difference between pretest and posttest scores (p < .05), accompanied by a very large effect size (r = 0.764). These results indicate that AR-Based Flashcards provide substantial learning benefits by offering engaging, interactive, and visually enriched input that supports vocabulary comprehension and retention. Pedagogically, AR-based instruction should be reinforced through brief consolidation tasks and differentiated scaffolding, while schools should ensure device availability, technical readiness, and teacher preparation to support effective implementation. Future research is recommended to employ comparative designs with larger samples, include delayed posttests, and examine engagement or motivation to better explain AR’s long-term effects.